2012
DOI: 10.1080/17542863.2011.554030
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and the maintenance of conformity: Japanese sojourner women

Abstract: Asian immigrant women have the lowest utilization of mental health services of any ethnic minority (Garland, Lau, Yeh & McCabe 2005). Because help seeking for distress occurs within social networks, we examined how social networks supported or disabled help seeking for Japanese sojourners living in the US. Unfortunately, most of the literature about Japanese social relationships focuses on men in organizational settings. This study used intensive ethnographic interviewing with 49 Japanese expatriate women to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…Although not in the initial aims, interview evaluations provided evidence that women found the CENI helpful in organizing traumatic experiences and articulating the meaning of low points. Several other studies using the CENI have reported similar findings (Saint Arnault & Fetters, 2011;Saint Arnault & Roels, 2012;Saint Arnault & Shimabukuro, 2012). It appears that by promoting self-awareness and meaning-making through empowerment and narrative self-disclosure, participants can gain insight to enable self-mastery and help-seeking decision-making.…”
Section: Discussionsupporting
confidence: 72%
“…Although not in the initial aims, interview evaluations provided evidence that women found the CENI helpful in organizing traumatic experiences and articulating the meaning of low points. Several other studies using the CENI have reported similar findings (Saint Arnault & Fetters, 2011;Saint Arnault & Roels, 2012;Saint Arnault & Shimabukuro, 2012). It appears that by promoting self-awareness and meaning-making through empowerment and narrative self-disclosure, participants can gain insight to enable self-mastery and help-seeking decision-making.…”
Section: Discussionsupporting
confidence: 72%
“…The following describes the interview with extracts from the transcripts to illustrate type of data obtained. Analysis of findings from the use of this interview are the subject of other publications (Saint Arnault & Roels, 2011; Shimabukuro & Saint Arnault, 2011). …”
Section: The Clinical Ethnographic Interviewmentioning
confidence: 99%
“…visa status, regionality, immigrant community characteristics, age of children, income, and length of their time abroad). In our sample, critical immigration issues that interacted together included the community organization, visa restrictions, and the developmental phases of the women, as we have described elsewhere (Saint Arnault, 2002; Saint Arnault & Roels, 2012). However, in this study, we also identified that women needed skills to balance self and community expectations.…”
Section: Discussionmentioning
confidence: 99%
“…We do know that Japanese women are less likely than White women to seek help for high levels of physical and emotional distress (Abe-Kim et al, 2007;Saint Arnault, 2002;Saint Arnault & Roels, 2012;Takeuchi, Hong, Gile, & Alegría, 2007;Takeuchi, Zane, et al, 2007;Williams, 2002). Previous research has shown that there are cultural and social factors besides distress level that can explain help seeking, such as emotional expression rules, fears about burdening others, and stigma related to emotional distress (Saint Arnault, 2009;Saint Arnault & Roels, 2012). This research adds to this science by illuminating how Japanese women view their symptoms as a reflection of a personal inability to mobilize resources or minimize risks in their daily lives, and they therefore find that they need to work harder to negotiate those factors.…”
Section: Discussionmentioning
confidence: 99%